2019
DOI: 10.1016/j.devcel.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A GBF1-Dependent Mechanism for Environmentally Responsive Regulation of ER-Golgi Transport

Abstract: SummaryHow can anterograde membrane trafficking be modulated by physiological cues? A screen of Golgi-associated proteins revealed that the ARF-GEF GBF1 can selectively modulate the ER-Golgi trafficking of prohaemostatic von Willebrand factor (VWF) and extracellular matrix (ECM) proteins in human endothelial cells and in mouse fibroblasts. The relationship between levels of GBF1 and the trafficking of VWF into forming secretory granules confirmed GBF1 is a limiting factor in this process. Further, GBF1 activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 81 publications
1
69
0
Order By: Relevance
“…Despite their length reduction, WPBs in Sec22b depleted cells normally recruited exocytotic components such as Rab27A and Slp4-a (Fig. S5), contrary to the enlarged WPBs in GBF1 ablated cells which failed to acquire post-Golgi cargo and Rab27A and which were secretion incompetent 62 . Although their short WPBs were still agonist responsive, Sec22b-depleted ECs secreted reduced levels of VWF through the regulated and basal secretory pathway ( Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite their length reduction, WPBs in Sec22b depleted cells normally recruited exocytotic components such as Rab27A and Slp4-a (Fig. S5), contrary to the enlarged WPBs in GBF1 ablated cells which failed to acquire post-Golgi cargo and Rab27A and which were secretion incompetent 62 . Although their short WPBs were still agonist responsive, Sec22b-depleted ECs secreted reduced levels of VWF through the regulated and basal secretory pathway ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study has identified GBF1 as a dynamic regulator of anterograde VWF trafficking and WPB morphology that, dependent on external/environmental cues, controls the flux of proteins (including VWF) from ER to Golgi 62 . Similar to what we observed after Sec22b 14 silencing, depletion of GBF1 led to accumulation of VWF in the ER and a reduction in the overall state of VWF proteolytic processing.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative high-throughput microscopy-based workflow, dubbed highthroughput morphometry (HTM), allows rapid quantification of the size of tens to hundreds of thousands of WPBs within thousands of endothelial cells (Ferraro et al, 2014). HTM has been applied for analytical purposes and in phenotypic screens (Ferraro et al, 2014;Ferraro et al, 2016;Ketteler et al, 2017;Lopes-da-Silva et al, 2019;Stevenson et al, 2014). In the present report, HTM was deployed to identify compounds that can induce a reduction of WPB size in Human Umbilical Vein Endothelial Cells (HUVECs).…”
Section: Screenmentioning
confidence: 99%
“…Short WPBs also form when VWF biosynthesis by endothelial cells is reduced, or following statin treatment, via Golgi fragmentation-independent and -dependent mechanisms, respectively (Ferraro et al, 2014;Ferraro et al, 2016). The metabolic status of endothelial cells also regulates WPB size through an AMPK-mediated signalling pathway (Lopes-da-Silva et al, 2019). Importantly, in vitro experiments have revealed that reducing WPB size results in the shortening of the VWF strings they generate and in much-reduced recruitment of platelets and soluble circulating VWF to the endothelial surface (Ferraro et al, 2014;Ferraro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation